Association between Sleep Duration and Measurable Cardiometabolic Risk Factors in Healthy Korean Women: The Fourth and Fifth Korean National Health and Nutrition Examination Surveys (KNHANES IV and V) - Hyeyeon Min; Yoo Jin Um; Bum Sup Jang; Doosup Shin; EunJoo Choi; Sang Min Park; Kiheon Lee (International Journal of Endocrinology)
Study Objectives. To examine the association between sleep duration and prevalence of metabolic syndrome (MetS) and its components in healthy Korean women. Design. Cross-sectional study, using the Fourth and Fifth Korean National Health and Nutrition Examination Surveys. Methods. Among 8505 women (25–70 years) from KNHANES IV and V, participants were classified into five sleep groups based on self-reported sleep duration. MetS and its components were defined using the criteria set forth in National Cholesterol Education Program-Adult Treatment Panel III. We used multivariate logistic regression analysis. Results. After adjusting for various confounders, shorter sleep duration (≤6 h) was found to have an association with low risk of reduced high-density lipoprotein cholesterol and increased triglycerides, whereas very long sleep duration was found to have high risk of increased triglycerides. However, abdominal obesity showed an opposite trend: short sleep duration was associated with higher risk of abdominal obesity than long sleep duration. Fasting glucose levels increased as sleep duration increased, but without significance. Moreover, blood pressure was not significantly associated with sleep duration. Consequently, MetS was less prevalent in those with short sleep duration. Conclusions. Sleep duration was positively associated with MetS, especially dyslipidemia and fasting hyperglycemia, but inversely associated with abdominal obesity.